Fenotip Kualitatif Kambing Lokal di Kecamatan Paguat Kabupaten Pohuwato Provinsi Gorontalo - Unti, Sri Valen; Sayuti, Muhammad; Ilham, Fahrul (Jurnal Sains Ternak Tropis, 2026)
This research aims to identify the qualitative phenotypes of local goats in Paguat District, Pohuwato Regency, Gorontalo Province. The samples observed consisted of 34 goats, comprising adult males and females. Variables observed include coat color, horn shape, ear shape, facial lines, and back lines. This analysis was conducted by calculating the percentage of occurrence of each morphological character relative to the total number of individuals observed using the relative frequency formula. The results of the study show that the dominant coat color is brown (47.06%), while the most common coat color combination is black, white, and brown (32.35%). The most common face line is convex (58.82%), and the dominant ear shape is drooping (73.53%). Most goats have long horns (64.71%) and no beard (85.29%), and the most common back line shape is straight (55.88%). The results of this study are expected to serve as a basis for the development of local goat selection and breeding programs aimed at increasing productivity and preserving regional germplasm. It is recommended to include genetic analysis and production performance to strengthen the relationship between morphological characteristics and the genetic potential of local goats, thereby supporting sustainable livestock development efforts in the region.Tujuan penelitian ini untuk mengidentifikasi fenotip kualitatif kambing lokal di Kecamatan Paguat, Kabupaten Pohuwato, Provinsi Gorontalo. Sampel yang diamati berjumlah 34 ekor kambing, terdiri dari jantan dan betina dewasa. Variabel yang diamati meliputi warna bulu, bentuk tanduk, bentuk telinga, garis muka, dan garis punggung. Analisis ini dilakukan dengan menghitung persentase kemunculan tiap karakter morfologis terhadap jumlah total individu yang diamati menggunakan rumus frekuensi relatif. Hasil penelitian menunjukkan warna bulu dominan adalah cokelat (47,06%), sedangkan kombinasi warna bulu yang paling umum adalah hitam, putih, dan cokelat (32,35%). Garis muka yang paling banyak ditemukan adalah cembung (58,82%), dan bentuk telinga yang dominan adalah menjuntai ke bawah (73,53%). Sebagian besar kambing memiliki tanduk panjang (64,71%) dan tidak berjanggut (85,29%) dan bentuk garis punggung yang paling umum adalah lurus (55,88%). Hasil penelitian ini diharapkan dapat menjadi dasar bagi pengembangan program seleksi dan pemuliaan kambing lokal yang berorientasi pada peningkatan produktivitas serta pelestarian plasma nutfah daerah. Disarankan untuk mencakup analisis genetik dan performa produksi guna memperkuat hubungan antara karakter morfologis dan potensi genetik kambing lokal, sehingga dapat mendukung upaya pengembangan ternak berkelanjutan di wilayah tersebut.